The Implementation of `Halal Logistics' During the COVID-19 Pandemic to Optimize the Transportation of Halal Products at PT BGR Logistics, Jakarta - Kurniawan, Johanes; Widyastuti Pratiwi, Sekar; Hanif Izzuddin, Jauhar; Kukuh Prasetyo, Afif; A. Nasution, Nursery; Iqbal Firdaus, Muhammad; Gafar, Abdul (KnE Social Sciences, 2023)
One of the several disruptions caused by the COVID-19 virus is business transportation and logistics problems. Handling logistics and quality service is one of the keys to the success of selling halal products on the market. PT BGR Logistics is currently implementing a halal logistics system, especially in the Warung Pangan application, which is one of its businesses. This study aimed to determine whether the implementation of halal logistics during the pandemic can improve service quality. Hopefully, this article can be used as a reference for the future of PT BGR Logistics and by the general public. This study used a quantitative method with a sample of Warung Pangan application users as buyers around JABODETABEK. Keywords: Halal Logistics, Halal Product, Disruption Covid 19,Service Quality